2017
DOI: 10.1590/0103-1104201711517
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à fragilidade em idosos hospitalizados: uma revisão integrativa

Abstract: This review aimed to synthesize and evaluate the production of knowledge about factors significantly associated with frailty in hospitalized elderly. Therefore, the Medical Literature and Retrieval System Online (Medline), Literatura Latino-Americana em Ciências da Saúde (Lilacs) and Índice Bibliográfico Español em Ciencias de la Salud (Ibecs) databases were consulted from 2012 to 2016, whose analysis of twenty articles identified the following factors associated with frailty: increased hospital and post-disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
8
0
10
Order By: Relevance
“…Moreover, it is necessary to understand that there is synergy of intrinsic and extrinsic factors, observing, thus, that advanced age, female gender, poverty, low education, smoking, low body mass index and presence of chronic diseases are predictive factors of frailty. 6 The detection of the Clinical and Functional Frailty Syndrome (CFFS) can be done through the observation of risk factors and appropriate assessment tools, for example, the Clinical and Functional Vulnerability Index-20 (CFVI-20), which has simple and accessible language, can be used by lay people and health professionals, and standardizes the classification of frailty by identifying it quickly. The CFVI-20 represents a national breakthrough, for it is the first Brazilian instrument to identify the frail elderly; and it is ranked among the four best in the world, being a reference in geriatrics when performing frailty screening.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is necessary to understand that there is synergy of intrinsic and extrinsic factors, observing, thus, that advanced age, female gender, poverty, low education, smoking, low body mass index and presence of chronic diseases are predictive factors of frailty. 6 The detection of the Clinical and Functional Frailty Syndrome (CFFS) can be done through the observation of risk factors and appropriate assessment tools, for example, the Clinical and Functional Vulnerability Index-20 (CFVI-20), which has simple and accessible language, can be used by lay people and health professionals, and standardizes the classification of frailty by identifying it quickly. The CFVI-20 represents a national breakthrough, for it is the first Brazilian instrument to identify the frail elderly; and it is ranked among the four best in the world, being a reference in geriatrics when performing frailty screening.…”
Section: Introductionmentioning
confidence: 99%
“…A high rate of hospital death was identified in the present study, in which one in 3.3 institutionalized old people who were hospitalized died in the hospital, considering that the majority of the sample was considered fragile, an integrative review found in the main factors related to fragility the highest mortality rate, where higher values in fragility scores are able to predict in-hospital mortality 24 .…”
Section: Resultsmentioning
confidence: 54%
“…Por ser considerada uma síndrome clínica e que aumenta com o avanço da idade, a Fragilidade de forma mais específica, além de resultar em um declínio acentuado das reservas fisiológicas do idoso e uma redução da eficiência da homeostase, vai impactar diretamente nas habilidades para executar as atividades de vida diárias 4 . Abaixo, a figura 1 apresenta as possíveis vias que levam à fragilidade.…”
Section: Fragilidade Em Idososunclassified